Biogas Production from Anaerobic Fermentation of Palm Oil Mill Biomass - Wong, Florence; Chua, Han; Siew, Y.F. (Chemeca 2010, 2010)
Effective management of oil palm industrial wastes remains a formidable challenge for palm millers. The traditional pond system for treatment of POME has increasingly come under the criticisms of DOE for the high level of methane or biogas emission into the atmosphere. Since methane is one of the major contributors to GHG, there is an urgent need for systematic assessment and control of its emission from the treatment plant sites into the atmosphere. One possible approach would be to carry out the POME treatment in an enclosed space and the gas produced can be separated and utilized as a biofuel.Studies have shown that POME is a potential source for biogas production.This present study focused on the anaerobic fermentation of POME, EFB and a mixture of both respectively, to determine the capability of biogas production. The preliminary results showed that the presence of EFB stimulated the yield and rate of formation of biogas from the anaerobic fermentation of POME by almost 3-fold 5-fold respectively. Further studies are being conducted to determine the optimum ratio of POME and EFB mixture for biogas production. The effect of other palm residues from the palm oil processing plant including the decanter solid (DS) on the biogas production from the POME fermentation is also reported. Anaerobic digestion process could provide an alternative means to treat the three major waste products of palm oil mills simultaneously and convert them into valuable green energy and organic compost following further treatment of the fermented residues.